Transformando 'verdades abstratas' em 'verdades concretas': uma análise sobre a metodologia econômica de John Stuart Mill - Mattos, Laura Valladão de (Estudos Econômicos (São Paulo), 2004)
We aim at explaining Mill's view on the transformation of the 'abstract truths' of the science of political economy - obtained by using the 'economic man' abstraction - in 'concrete truths', which could be used both to predict events and as support for policy decisions. We argue that it would not only be necessary to 'humanize' the 'economic man' by taking in account several human motivations that are not considered by the science of political economy, but also to take in account the institutional peculiarities of each case. We conclude that despite Mill's success on his attempts to transform 'abstract' in 'concrete' truths, his methodological advices are too vague and insufficient to guide us in this important issue.